To slip out of the geometric straitjacket: Using the tunnel method to promote irregularity in wallpaper patterns - Korn, Mirjam (FormAkademisk, 2023)
The tunnel method is a technique employed in the design of wallpaper patterns to facilitate the hanging process while maintaining the integrity of the pattern. It can be utilised in both the reconstruction of historical patterns and the creation of new ones. I have explored the potential of this method since 2006, and in my latest project, I had the opportunity to document its application in Swedish wallpaper studios and endeavour to understand its historical background regarding cultural and printing conditions. By testing the effect of applying the method to wallpaper patterns, I explored its possibility of generating distinctive effects within the pattern when the wallpaper is installed. In this way, the user can actively participate in determining the degree of variation in the pattern during the installation process, either by embracing serendipity or by making deliberate choices. The purpose is to promote wallpaper patterns with greater variation and wallpapers made from sustainable materials. Although this investigation led to several different ways of utilising the tunnel method, there is still much to be explored in this field. By sharing my work, I aim to motivate more people to explore the potential of the tunnel method. Notably, the communication of its functionality to customers and its integration within the cultural context remain limited.